Success Driven: Student Motivation Actions in Teaching and Learning - J. Grant Coke, Monique (Journal of Human Psychology, 2022)
The purpose of this topic is to add to the body of good teaching and learning that helps create the conditions for more critical thinking and practice skills that enable, keep students interested, and consistently motivate them. Teachers now have a greater focus on implementing motivational learning and studying strategies that are more relevant to the processes of teaching and learning thanks to new methodologies, which have further enhanced instructional strategies for teaching and learning. Positive school cultures that are long-lasting will result from these new methods and strategies. According to the authors, educators have been impacted by evidence-based practice and data-based decision making within the educational system. As a result, there is a growing need for educators to learn more about these resources that are relevant to students and can lead to greater success. These applicable interventions have a positive effect on students, and the information that helps them make decisions increases their response.
Keywords: teaching; critical thinking; motivation